What are the links between tree‐based farming and dietary quality for rural households? A review of emerging evidence in low‐ and middle‐income countries. Issue 2 (28th February 2022) - Vansant, Emilie C.; Mausch, Kai; Ickowitz, Amy; McMullin, Stepha; Karanja, Alice; Rasmussen, Laura Vang
Abstract: In most low‐ and middle‐income countries (LMICs), conventional agricultural policy promotes specialized production systems of carbohydrate‐rich crops to address hunger and food insecurity. For rural populations, however, increased landscape uniformity can reduce both agrobiodiversity and wild biodiversity, which can contribute to diet uniformity. Although maintaining diversity in and around agricultural systems is far from a new approach, there is growing empirical attention on the contribution of trees on/around farms to dietary quality. While recent research suggests that forests can contribute to improved diets, there is only emerging evidence on how incorporating trees into farming systems not only benefits nature but also positively affects the diets of rural households. This review synthesizes the existing empirical research on the linkages between different types of tree‐based farming systems and indicators of dietary quality in LMICs. The objective is to build a foundation for future research that supports sustainable production systems with dual benefits for people and the natural environment. The small, yet heterogeneous literature pool ( n  = 36 studies) reflects the high variance in how trees on/around farms are examined across cultural and geographical contexts. Our analysis identifies three major outcomes: (a) managing tree‐based farming systems for both direct provision of wild and cultivated foods, as well as income used to purchase foods, may give households more strategies for dietary diversification and improve dietary quality; (b) the relationship between different tree‐based farming systems and dietary quality is moderated by socio‐economic and biophysical factors at the national, landscape and household levels; and (c) indigenous populations engaged in traditional forms of subsistence‐oriented tree‐based farming seem to maintain high levels of dietary diversity, indicating the importance of local knowledge and biodiversity stewardship to maintain these food sources in the face of commercial agricultural expansion. Our synthesis of existing evidence highlights a need for a more nuanced understanding of how different types of tree‐based farming systems contribute to dietary quality. Combining research methods from the domains of agriculture, forestry and nutrition can lead to more precise measurement of tree‐based farming/diet linkages, and in doing so, support programs promoting increased landscape and dietary diversity in LMICs. Read the free Plain Language Summary for this article on the Journal blog. Abstract : Read the free Plain Language Summary for this article on the Journal blog.